2021
DOI: 10.25081/josac.2021.v30.i1.6576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic manures, PGPR and micronutrients on yield and quality enhancement in ajwain (Trachyspermum ammi L)

Abstract: Experiments were conducted for two consecutive years during 2017-19 to study the effect of organic manures, PGPR and micronutrients on yield and quality of ajwain seed. Farm yard manure (FYM) and vermicompost (VC) were used as organic sources at 50% and 75% recommended dose of nitrogen (RDN) as basal dose. PGPRs namely Azospirillum lipoferum, Bacillus megaterium and Frateuria aurantia were used for seed priming. Micronutrients namely ZnSO4 and Fe2SO4 were applied thrice as foliar application @ 0.5% first befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…Similar findings reported in Alam (2017) Assessment of Productivity Dyanamics of Chickpea based Intercropping with Linseed and Seed Spices on BBF under Organic Cultivation zone with higher metabolic activity at the cellular level might have enhanced the nutrient uptake and accumulation in the vegetative parts, which in turn resulted in higher dry mater content in ajwain. Similar findings reported by (Thanuja et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…Similar findings reported in Alam (2017) Assessment of Productivity Dyanamics of Chickpea based Intercropping with Linseed and Seed Spices on BBF under Organic Cultivation zone with higher metabolic activity at the cellular level might have enhanced the nutrient uptake and accumulation in the vegetative parts, which in turn resulted in higher dry mater content in ajwain. Similar findings reported by (Thanuja et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…The enormous diversity present across all the traits is indicated by the mean square sum, which for all the qualities was found to be highly significant. Moderate values of the genotypic and phenotypic coefficient of variation were discovered for Singh et al (2019) [14] , Nagar et al (2018) [11] , Subramaniyam et al (2018) [16] , and Ghanshyam et al (2015) [5] in the number of branches per plant, number of umbels per plant, number of umbelletes per umbel, number of seeds per umbel, seed yield per plant, biological yield per plant, test weight, and volatile oil (Table .1, Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Meena et al (2016) [9] obtained a similar result in relation to plant height. The number of branches per plant had a directly detrimental impect on seed yield per plant, according to studies by Ghanshyam et al (2015) [5] and Subramaniyam et al (2018) [16] . While Ghanshyam et al (2015) [5] and Subramaniyam et al (2018) [16] reported identical results for the number of umbels per plant, Ghanshyam et al (2015) [5] found similar results for the number of umbelletes per umbel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative link of days to maturity with seed yield per plant is due to sudden increase in the temperature which led to sucking pest (aphids) infestation on the crop during the investigation. The reports of Ranjeetha et al (2020 and 2021) [21,22] in ajwain genotypes, Ghanshyam et al (2015) [10] and Faravani et al (2018) [8] in ajwain genotypes/ accessions, Kassaun et al (2013) [14] , Jain et al (2013) [13] , Patahk et al (2014) [17] and Meena et ~ 508 ~ al. (2014) [18] in coriander accessions, Singh et al (2016) [25] and Gurjar et al (2016) [12] in fenugreek genotypes and Bahraminejad et al (2011) [2] in cumin ecotypes supports the present findings.…”
Section: Genotypic and Phenotypic Correlation Coefficient Analysismentioning
confidence: 99%